Data for daily activity and social behaviour of Hungarian alpacas at spring - Bodnár, Ákos; Nagy, Máté Farkas; Faragó, Loretta Barbara; Pajor, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
This article provides data for daily activity and social behaviour of alpacas (mare: n = 6; stallion: n = 4), based on observations at April. Our goal was to observe the occurrences and proportion of the behaviour elements at different parts of the day. In addition, reactions of the animals to the extreme environmental factors (heavy rain, very strong wind) were also recorded. Recordings of a security camera were used to collect data at a Hungarian alpaca farm. Using the security camera, we could observe the animals without external interference. Current behaviour of the animals was recorded 4 times on each day of April. There is only few numbers of literatures about behavioural studies of alpacas. Therefore, it was important to record all the interesting events, which were occurred during the investigation. Based on our results one can tell, that the proportion of grazing behaviour (41-51% in average of both sexes), proportion of resting/ruminating behaviour (15-22% in average of both sexes) and proportion of moving behaviour (17-27% in average of both sexes) was the highest during the investigated month. Highest proportion of grazing behaviour was observed in the morning and midday period at both sexes. Further and similar studies need to define the daily rhythm of the animals in other seasons, too.
Keywords: alpaca; daily activity; behaviour